Flexible horizontal piezoelectric energy generator for sea wave applications - Ahmad Syafiq, Deraman; Mohd Rusllim, Mohamed; Wan Ismail, Ibrahim; Leung, Puiki (Elsevier Ltd, 2023)
Energy harvesting from the environment becomes a valuable technology, especially for sea wave applications, in which it usually ends up wasted despite its potential to be harvested. Due to its wide availability and high energy density, piezoelectric energy harvesting (PEH) is becoming popular for flexible energy harvesting. This paper presents a flexible horizontal piezoelectric (FHP) energy harvester to harvest energy from the surface of sea wave. The harvester is made of bimorph piezoelectric devices; they are utilised to amplify and convert the collected mechanical vibrations into electrical power. A finite element model is established from ANSYS simulations to solve the iteration method by generating resonance frequency (fr). Then, Taguchi method, SN ratio and the ANOVA approach were used by considering the input variable of fr to estimate the optimum performance through control factors; number of blade, length and thickness. From the performance test result, it is proven that the higher numbers of blade including length, and minimum numbers of thickness significantly improve the significant level, α = 0.05% of ANOVA. Three prototypes are developed with approximate body dimensions through the resonance frequency perform and generate a 160.3 Hz on blade dimensions of 10 × 300 × 0.2 mm, with a piezoelectric (PZT) on its surface. This particular study shows that the potential of output power is generated from sea wave surface through a significant relationship between length, thickness, and blade design. This research develops a novelty for energy harvesting from flexible piezoelectric generator on sea wave application that could be easily install on offshore platform.